(untitled) (Eurasian Journal of Learning and Academic Teaching, 2022)
This article is based on the need to increase the social activity of young people and the fact that increasing the social activity of young people is a purposeful organizational and pedagogical process, in which the need to improve and enrich the qualities of social activity is formed in young people.